Glutamatergic signaling and low prodynorphin expression are associated with intact memory and reduced anxiety in rat models of healthy aging - Ménard, Caroline; Quirion, Rémi; Bouchard, Sylvain; Ferland, Guylaine; Gaudreau, Pierrette (Frontiers in Aging Neuroscience, 2014)
The LOU/C/Jall (LOU) rat strain is considered a model of healthy aging due to its increased longevity, maintenance of stable body weight (BW) throughout life and low incidence of age-related diseases. However, aging LOU rat cognitive and anxiety status has yet to be investigated. In the present study, male and female LOU rat cognitive performances (6-42 months) were assessed using novel object recognition and Morris Water Maze tasks. Recognition memory remained intact in all LOU rats up to 42 months of age. As for spatial memory, old LOU rat performed similarly as young animals for learning acquisition, reversal learning and retention. While LOU rat BW remained stable despite aging, 20-month-old ad-libitum-fed (OAL) male Sprague Dawley rats become obese. We determined if long-term caloric restriction (LTCR) prevents age-related BW increase and cognitive deficits in this rat strain, as observed in the obesity-resistant LOU rats. Compared to young animals, recognition memory was impaired in OAL but intact in 20-month-old calorie-restricted (OCR) rats. Similarly, OAL spatial learning acquisition was impaired but LTCR prevented the deficits. Exacerbated stress responses may favor age-related cognitive decline. In the elevated plus maze and open field tasks, LOU and OCR rats exhibited high levels of exploratory activity whereas OAL rats displayed anxious behaviors. Expression of prodynorphin (Pdyn), an endogenous peptide involved in stress-related memory impairments, was increased in the hippocampus of OAL rats. Group 1 metabotropic glutamate receptor 5 and immediate early genes Homer 1a and Arc expression, both associated with successful cognitive aging, were unaltered in aging LOU rats but lower in OAL than OCR rats. Altogether, our results, supported by principal component analysis and correlation matrix, suggest that intact memory and low anxiety are associated with glutamatergic signaling and low Pdyn expression in the hippocampus of non obese aging rats.